Gambaran Perubahan Fisik dan Psikologis pada Wanita Menopause Di Posyandu Desa Pabelan - Hekhmawati, Selvia; , Agus Sudaryanto, S.Kep., Ns., M.Kes (2016)
Menopause is a transition period of menstruation becomes no longer having periods. Women who have entered menopause is likely to decline especially changes in physical health. Hot flush, the vagina becomes dry, sagging skin and wrinkles are examples of physical changes. Physical changes as a result of menopause can affect the psychological state of menopausal women such as irritability, anxiety, stress and depression. According to data taken in Posyandu Pabelan 8 of 10 menopausal women have experienced physical and psychological changes. The purpose of this study to describe the physical and psychological changes in postmenopausal women at Posyandu Pabelan. The method used quantitative descriptive design with cross-sectional approach and the sampling technique snowball sampling. In this study obtained 75 respondents, the instrument using a questionnaire based on the theory. Using univariate analysis were assisted SPSS 17 for windows. The results of the study physical changes most often experienced in menopausal women are hot flush 81,3%, insomnia 65.3%, 58.7% vagina becomes dry, rheumatic pain and joint pain 57.3%. Psychological changes most often experienced in postmenopausal women 81.3% irritability, anxiety 64%, 44% decreased memory. The conclusion of this study is the most common physical changes experienced by menopausal women are hot flush, while the psychological changes often experienced by respondents is irritability.